Development of framework for armoured vehicle assembly line efficiency improvement by using simulation analysis: Part 1 - A. S. H. M., Yasir; N. M. Z. N., Mohamed; A. Q., Basri (IOP Publishing, 2019)
Efficiencies and the productivity of the assembly line are crucial in the manufacturing sector. It is very unusual opportunity to visualise and analyse the production system, which used in defence manufacturing sector. This research study focuses on the performance of an existing production line for Malaysia's automotive defence manufacturing industry. The main issues that arise are first, the delivery is always behind the schedule and second, the human factor that contributes to the increase of rejected parts and slow down the production line. WITNESS simulation will be utilised to analyse the dynamic issues associated with the whole performance of the manufacturing system. A methodology for production layout improvement will bring into notice. DELMIA simulation can improve employee's working condition, which is to optimise the production line efficiency. The assembly line can be better in many ways, for example, the arrangement of working layout, the summit of the workplace and massive machines handling method by the worker. All of these are imperative to increase the efficiency of the employees. Continuous improvement of the proposed methodology includes progress in model design, training of operators, follow-up of implementing changes and investigations in the measurement of manufacturing line efficiencies.